Rancang bangun alat uji pompa sentrifugal bahan bakar solar sebagai media pembelajaran dan praktikum mahasiswa Program Studi Teknik Mesin Universitas Muhammadiyah Pontianak skala laboratorium - Gunarto Gunarto; Suje'i Suje'i; Doddy Irawan; Eko Julianto (Universitas Muhammadiyah Metro, 2021)
This study aims to produce a diesel oil transfer device using a pump as a learning medium as well as a practical pump course for students of the Mechanical Engineering Study Program, University of Muhammadiyah Pontianak. This design needs to be made as an effort to stimulate learning motivation, improve students' understanding and thinking skills in pumping courses. The research stages are carried out by designing the design and manufacture or assembling of the diesel oil transfer device into a unified whole, as well as testing the tool so that it can be used for learning media and practicum. Data collection and retrieval is adjusted to the test instrument instrument. The result of this research is a learning and practical media tool to test the characteristics of diesel oil centrifugal pumps. This oil transfer device can operate properly and has met the standards of the pump used. This media can be used as a lecturer to facilitate the learning process for pump courses. In addition, this tool is worthy of being used as a practicum tool for centrifugal pump performance specifically for diesel oil pumps.